2014
DOI: 10.1586/17476348.2015.996132
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary aspergillosis in patients with influenza infection: report of two cases and systematic review of the literature

Abstract: Superinfection or coinfections are major causes of morbidity and mortality in patients with influenza. There are limited data on invasive pulmonary aspergillosis (IPA) in this setting. We conducted a systematic review of the literature for patients with IPA following influenza infection. A total of 68 patients (two reported from our institution and 66 identified by literature review) were analyzed. The majority of patients had underlying comorbid illnesses. Overall, the mortality rate in this cohort was 47%. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 46 publications
2
43
1
2
Order By: Relevance
“…Of 11 immunocompetent patients with invasive aspergillosis and Influenza in a recent case series, 6 (55%) died (van de Veerdonk et al, 2017). Mortality differences were not observed in patients with and without hematologic malignancies in another review (Alshabani et al, 2015). In 1–2% of mechanically ventilated, non-neutropenic patients, respiratory cultures will show Aspergillus species.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Of 11 immunocompetent patients with invasive aspergillosis and Influenza in a recent case series, 6 (55%) died (van de Veerdonk et al, 2017). Mortality differences were not observed in patients with and without hematologic malignancies in another review (Alshabani et al, 2015). In 1–2% of mechanically ventilated, non-neutropenic patients, respiratory cultures will show Aspergillus species.…”
Section: Discussionmentioning
confidence: 88%
“…Two systematic reviews of invasive aspergillosis complicated by Influenza infection reported 68 and 57 total cases (Alshabani et al, 2015; Crum-Cianflone, 2016a). One review of immunocompetent and immunocompromised patients with Influenza and IPA reported Influenza A in 93% of cases, with the majority of these having H1N1.…”
Section: Discussionmentioning
confidence: 99%
“…Either false positives (patients diagnosed as pneumonia whereas only colonized) or a specific, not yet described, influenza-P. aeruginosa co-infection (Shah at al., found similar incidence of P. aeruginosa [12]) could explain such high rates of P. aeruginosa pneumonia, especially if they truly are community acquired. The high rate of co-infection due to Aspergillus (7.2%) is also surprising: although invasive pulmonary aspergillosis has been described in patients with H1N1-related pneumonia, it has rarely been *Correspondence: charles-edouard.luyt@psl.ap-hop-paris.fr 1 Service de Réanimation Médicale, Groupe Hospitalier La Pitié-Salpêtrière, Assistance Publique-Hôpitaux de Paris, Paris, France Full author information is available at the end of the article described as a community-acquired co-infection but more as a secondary fungal infection, even in immunosuppressed patients [13,14]. Although this study focused on community-acquired co-infection (and in fact excluded patients admitted from nursing homes or other healthcare facilities), the high incidences of P. aeruginosa and Aspergillus as pathogens responsible for co-infection is in favor of a mix of community-acquired infections and secondary bacterial and fungal infections.…”
mentioning
confidence: 99%
“…4,5 In addition to higher risk of lower respiratory tract infection by these viruses, there is an increased risk of coinfection or superinfection with bacteria and fungi. 60 Approach to the diagnosis of pulmonary complications after hematopoietic stem cell transplant There are no standard guidelines for the evaluation of pulmonary complications after HSCT. Most studies in the literature are based on retrospective analysis of single center studies.…”
Section: Viral Pneumoniamentioning
confidence: 99%